Analisis Implikasi dari Fenomena Perkawinan Dini yang Terjadi di Kalangan Gen Z Terhadap Sistematika Hukum Sesuai Undang-Undang No.16 Tahun 2019 - Dinar Aura Suryaputri; Yerina Gultom; Nada Nurhasnah Yudiana; Rizka Alkautsar; Rhafa Nur Afifah; Mahipal (Al Fuadiy Jurnal Hukum Keluarga Islam, 2025)
This study examines the prevalence of early marriage among Generation Z in Indonesia and its legal implications under Law No. 16 of 2019 and Islamic Law. Using a qualitative normative approach, the research analyzes literature from legal documents, journals, and government reports. Findings indicate that despite the legal minimum marriage age of 19, early marriages persist due to socio-economic factors, religious misinterpretations, and judicial dispensations. The study highlights contradictions between statutory law and Islamic Law, which emphasizes readiness over strict age limits. Recommendations include stricter dispensation oversight, community education, and inter-sectoral collaboration to protect children's rights